Food Diversity and Diet Quality as Determinants of Metabolic Syndrome in Fishermen Communities - Besti Verawati; Rina Oktasari; Ai Kustiani; Nuryani Nuryani (Media Publikasi Cendekia Indonesia, 2026)
This study aimed to assess the association of food diversity and diet quality with metabolic syndrome (MetS) among fishermen communities in coastal Indonesia. An analytical observational case–control design was conducted among 120 adult fishermen (60 MetS cases and 60 controls) in Lhokseumawe, Aceh. MetS was diagnosed based on International Diabetes Federation criteria. Dietary diversity was measured using the Individual Dietary Diversity Score (IDDS) through two non-consecutive 24-hour recalls, and diet quality was evaluated using the Healthy Diet Indicator (HDI). Bivariate and multivariate logistic regression analyses were performed to determine dietary predictors of MetS, adjusting for age, gender, and physical activity. Fishermen with MetS showed a higher prevalence of low dietary diversity (IDDS ≤3: 33.3% vs. 20.0%, p = 0.048) and poor diet quality (HDI ≤4: 58.3% vs. 33.3%, p = 0.010) compared to controls. Multivariate analysis confirmed that low dietary diversity (AOR = 2.10; 95% CI: 1.05–4.50; p = 0.038) and poor diet quality (AOR = 2.80; 95% CI: 1.25–6.20; p = 0.012) were independently associated with MetS. Socioeconomic factors, including age, household size, education, and income, were not significantly associated with MetS. Low dietary diversity and poor diet quality are significant predictors of MetS among fishermen. Nutrition interventions aimed at improving both dietary variety and overall diet quality may effectively reduce metabolic risks in labor-intensive coastal communities.